2021
DOI: 10.1186/s13071-021-04852-w
|View full text |Cite
|
Sign up to set email alerts
|

iSeq 100 for metagenomic pathogen screening in ticks

Abstract: Background Ticks are blood-sucking ectoparasites that play a pivotal role in the transmission of various pathogens to humans and animals. In Korea, Haemaphysalis longicornis is the predominant tick species and is recognized as the vector of pathogens causing various diseases such as babesiosis, borreliosis, rickettsiosis, and severe fever with thrombocytopenia syndrome. Methods In this study, the targeted high-throughput sequencing of the 16S rRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
(49 reference statements)
1
8
0
Order By: Relevance
“…This study also found that all samples from military training centers in Gangwon Province contained Coxiella (Fig. 2), identified as a Coxiella-like endosymbiont (AB001519), consistent with previous studies in the same region (Lee et al 2004;Kim et al 2021a;Sang et al 2022).…”
Section: Discussionsupporting
confidence: 91%
“…This study also found that all samples from military training centers in Gangwon Province contained Coxiella (Fig. 2), identified as a Coxiella-like endosymbiont (AB001519), consistent with previous studies in the same region (Lee et al 2004;Kim et al 2021a;Sang et al 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Our method can theoretically detect all potentially pathogenic taxa in samples and simultaneously analyze 96 samples at once. The approximate cost of one run of the iSeq 100 machine is US$ 2000, which takes 18 h to complete [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of high-throughput sequencing allows the use of a metagenomic approach to detect all prokaryotic and eukaryotic species in a sample in a single sequencing run at a low cost [ 17 19 ]. In this study, we used amplicon deep sequencing of the 12S rRNA and 18S rRNA genes to identify the mammalian hosts of the tsetse fly and associated eukaryotic pathogens (including Trypanosoma spp.…”
Section: Introductionmentioning
confidence: 99%
“…marginatum feeding on yaks in Tibet, China. mNGS has been successfully used to identify known and/ or unknown microorganisms in arthropods [38,39], thus enabling analysis of microorganism diversity. By mNGS, the most abundant bacteria identified in ticks include Rickettsia spp., Coxiella spp., Francisella spp., and "Candidatus Midichloria mitochondrii" [40].…”
Section: Discussionmentioning
confidence: 99%